2021
DOI: 10.1136/bmjopen-2020-040912
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution, physical activity and ischaemic heart disease: a prospective cohort study of interaction effects

Abstract: ObjectiveTo assess a possible interaction effect between physical activity and air pollution on first incidence of ischaemic heart disease (IHD).DesignProspective cohort study.SettingUmeå, Northern Sweden.ParticipantsWe studied 34 748 adult participants of Västerbotten Intervention Programme cohort from 1990 to January 2014. Annual particulate matter concentrations (PM2.5 and PM10) at the participants’ residential addresses were modelled and a questionnaire on frequency of exercise and active commuting was com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Since exposure to PM2.5 in Umeå has been shown to be associated with an increased risk of developing dementia (Oudin et al 2018) as well as the incidence of cardiovascular disease (Raza et al 2021), healthier older adults may be over-represented at higher exposure levels. Competing risks and selection may therefore be a source of bias in the present study, especially in older ages, which could theoretically at least partly explain our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Since exposure to PM2.5 in Umeå has been shown to be associated with an increased risk of developing dementia (Oudin et al 2018) as well as the incidence of cardiovascular disease (Raza et al 2021), healthier older adults may be over-represented at higher exposure levels. Competing risks and selection may therefore be a source of bias in the present study, especially in older ages, which could theoretically at least partly explain our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Endes et al examined physical activity as a modifier of the association between air pollution and arterial stiffness in 2823 adults (50-81 years old), they found that the probability of having an increased risk of arterial stiffness was higher with high PM 10, PM 2.5, NO 2 in inactive subjects but not in physically active participants [57]. Other studies conducted on the risk of ischemic heart disease and stroke suggesting that physical activity may reduce PM 2.5 induced risk of cardiovascular events in subjects who are involved in physical activity above 2 times/week [58,59]. Studies conducted on animal models tried to investigate the protective role of physical activity against the harmful effects of air pollution.…”
Section: Long-term Effectsmentioning
confidence: 97%
“…However, these increased risks were only present in subjects that exercised at most once a week and no interaction effect between physical activity and PM 2.5 exposure was found, suggesting that physical activity may reduce PM 2.5 induced risk of incident cardiovascular events. A further study by Raza et al, including 34,748 Swedish adults, confirmed these results by showing that being physically active at least twice a week was associated with decreased risk of incident ischemic heart disease among subjects exposed to high levels of PM 2.5 (HR 0.60, 95% CI 0.44–0.82) and PM 10 (HR 0.55, 95% CI 0.4–0.76) [ 106 ]. Conversely, this effect was weaker/not present among subjects exposed to low levels of PM 2.5 (HR 0.94, 95% CI 0.72–1.22) and PM 10 (HR 0.99, 95% CI 0.76–1.29).…”
Section: Recent Epidemiological Evidence On the Association Between Physical Activity Long Term Exposure To Air Pollution And (Cardiovascmentioning
confidence: 81%